2008
DOI: 10.1103/physrevb.78.132510
|View full text |Cite
|
Sign up to set email alerts
|

Low-temperature proximity effect in clean metals with repulsive electron-electron interaction

Abstract: Theories of proximity effect in layered superconductor-normal-metal ͑SN͒ structures usually deal with a hypothetic normal metal with no direct repulsive interaction between electrons and with finite temperatures often close to the superconductor critical temperature. We present an asymptotic solution of the Gor'kov equations in the opposite low-temperature limit for a clean normal metal with a repulsive interaction between electrons. The order parameter in the metal exhibits a power-law decay, ⌬͑x͒ ϰ / x, as a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…This statement is valid for distances z smaller than both the thermal decay length ξ T = hv N /kT and the mean-free path l = v N τ , where τ represents the mean time between impurity scattering events [18]. Beyond these distances, the range of the proximity effect will be dictated by the smaller of these two lengths [22][23][24].…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…This statement is valid for distances z smaller than both the thermal decay length ξ T = hv N /kT and the mean-free path l = v N τ , where τ represents the mean time between impurity scattering events [18]. Beyond these distances, the range of the proximity effect will be dictated by the smaller of these two lengths [22][23][24].…”
Section: Introductionmentioning
confidence: 91%
“…Within the framework of analytical studies and numerical calculations based on the self-consistent Bogoliubov-de Gennes (BdG) equations it was demonstrated that at low (zero) temperatures, the decay of the pair amplitude within the NM deviates from exponential behavior. Instead, the behavior observed in the NM in the ballistic regime follows a power-law decay [9,[15][16][17][18]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation